2014
DOI: 10.1016/j.toxlet.2014.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the masked mycotoxin deoxynivalenol-3-glucoside in pigs

Abstract: Plants can metabolize the Fusarium mycotoxin deoxynivalenol (DON) by forming the masked mycotoxin deoxynivalenol-3-β-D-glucoside (D3G). D3G might be cleaved during digestion, thus increasing the total DON burden of an individual. Due to a lack of in vivo data, D3G has not been included in the various regulatory limits established for DON so far. The aim of our study was to contribute to the risk assessment of D3G by determination of its metabolism in pigs. Four piglets received water, D3G (116 μg/kg b.w.) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
130
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 42 publications
10
130
0
2
Order By: Relevance
“…These findings correlate well with those of Nagl et al (2012Nagl et al ( , 2014, underlining that the majority of oral administrated D3G was recovered as DON in feces. In vivo, the conversion of D3G to its toxic aglycone may occur in the distal part of the gut, while ingested DON is absorbed in the proximal part of the small intestine (Maresca 2013).…”
Section: Figsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings correlate well with those of Nagl et al (2012Nagl et al ( , 2014, underlining that the majority of oral administrated D3G was recovered as DON in feces. In vivo, the conversion of D3G to its toxic aglycone may occur in the distal part of the gut, while ingested DON is absorbed in the proximal part of the small intestine (Maresca 2013).…”
Section: Figsupporting
confidence: 82%
“…It has been described that D3G is considerably less bioavailable in mammals when compared to DON. Indeed, following oral administration, only small percentage of applied dose of D3G was found in urine in rats and piglets (Nagl et al 2012(Nagl et al , 2014. Moreover, in a human volunteer consuming a diet naturally contaminated with D3G, the masked mycotoxin could not be detected in urine (Warth et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(20). Evidence that DON-3G is almost completely hydrolyzed in the digestive tract of rats, pigs, and humans has been presented (21)(22)(23).…”
mentioning
confidence: 99%
“…The bioavailability of D3G is a subject of ongoing research . The latest studies on rats and pigs indicated that D3G partly contributes to the total DON intake (Nagl et al ., 2012;Nagl et al ., 2014) . Authors of another study dealing with the bioavailability of masked mycotoxins confirmed that DON conjugates were effectively deconjugated by the human colonic microbiota releasing parent DON (Dall'Erta et al ., 2013) .…”
mentioning
confidence: 99%